PREVALENCE OF HLA-B27 AMONG PATIENTS WITH ANKYLOSING SPONDYLITIS IN SULAIMANI PROVINCE - Muhammed, Chawarwan Qassim; Mirza, Raouf Rahim (Journal of Sulaimani Medical College, 2024)
Background Ankylosing spondylitis is a prototype of a spondyloarthritis family of diseases characterized by chronic infl ammation of the sacroiliac joints, spine, and entheses, mostly affecting young men. The prevalence of AS varies with the frequency of HLA-B27 in the population. A strong association between AS and the HLA-B27 haplotype has been reported, and it is estimated that up to 90% of patients with AS harbor the HLAB27 haplotype. Objective HLA-B27 is incorporated in the new ASAS classifi cation criteria for diagnosing axial SpA/AS; therefore, determining the prevalence of HLA-B27 among AS patients in Sulaimani Province could affect the early recognition and treatment of the disease while preventing undesired complications and preserving the quality of patients’ lives. Patients and Methods This cross-sectional study incorporated ninety-two patients who met the ASAS and mNY criteria for AS. The patients were visitors of The Rheumatology Centere for Biologic Therapies-Shaheed Hemin Hospital. The data collection process extended from the 15th of October 2021 to the 20th of April 2022. Results Of the total of 92 patients (64 males and 28 females), the prevalence of HLA-B27 was 65.2%. The mean age of the diagnosis of AS was 32.07 years. The male-to-female ratio of AS was 2.29:1. Meanwhile, the ratio of males to females with positive HLA-B27 was 2.33:1. The most prevalent symptom was lower back pain in all the patients comprising 92.4%, followed by enthesitis 40.2%, peripheral arthritis 22.8%, and Uveitis 19.6%. Conclusion This study reported the prevalence of HLA-B27 at 65.2% in Sulaimani Province among AS patients. This fi gure could be dependable in diagnosing and properly treating the disease, particularly in those in the early stages who have not yet developed radiological evidence of AS.
Keywords: Ankylosing Spondylitis; HLA-B27; Axial SpA; Seronegative Spondyloarthropathy